Abdominal Aortic Calcifications Predict Survival in Peritoneal Dialysis Patients. Issue 5 (September 2018) - Mäkelä, Satu; Asola, Markku; Hadimeri, Henrik; Heaf, James; Heiro, Maija; Kauppila, Leena; Ljungman, Susanne; Ots-Rosenberg, Mai; Povlsen, Johan V.; Rogland, Björn; Roessel, Petra; Uhlinova, Jana; et al.
Background: Peripheral arterial disease and vascular calcifications contribute significantly to the outcome of dialysis patients. The aim of this study was to evaluate the prognostic role of severity of abdominal aortic calcifications and peripheral arterial disease on outcome of peritoneal dialysis (PD) patients using methods easily available in everyday clinical practice. Methods: We enrolled 249 PD patients (mean age 61 years, 67% male) in this prospective, observational, multicenter study from 2009 to 2013. The abdominal aortic calcification score (AACS) was assessed using lateral lumbar X ray, and the ankle-brachial index (ABI) using a Doppler device. Results: The median AACS was 11 (range 0 – 24). In 58% of the patients, all 4 segments of the abdominal aorta showed deposits, while 19% of patients had no visible deposits (AACS 0). Ankle-brachial index was normal in 49%, low (< 0.9) in 17%, and high (> 1.3) in 34% of patients. Altogether 91 patients (37%) died during the median follow-up of 46 months. Only 2 patients (5%) with AACS 0 died compared with 50% of the patients with AACS ≥ 7 ( p < 0.001). The adjusted hazard ratio for all-cause mortality was 4.85 (95% confidence interval [CI] 1.94 – 24.46) for aortic calcification (AACS ≥ 7), 2.14 for diabetes (yes/no), 0.93 for albumin (per 1 g/L), and 1.04 for age (per year). A low or high ABI were not independently associated with mortality. Conclusions: Severe aortic calcification was a strong predictor of all-cause mortality in PD patients. The evaluation of aortic calcifications by lateral X ray is a simple method that allows the identification of high-risk patients.